Increased Speed and Agility Through Ladder Drill Variations - Niqsanding Sanrijaya; Oce Wiriawan; Sapto Wibowo (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
This study aims to determine the effect of the ladder drill exercise with one foot in each and fight shuffle (group 1) and with the ladder drill with two feet in each and skiers (group 2) on increasing speed and agility. The method used in this research is Quasi Experiment. In this study, 30 samples were used which were divided into 3 groups which were given different treatments. This study uses the speed of measurement and agility. The results of this study showed that the speed and agility of the pretest and posttest results in group 1 showed an increase of 11% in speed and 14% in agility. while for group 2 there was an increase of 9% in speed and 16% in agility. Based on these results, it can be stated that the effect of the drill ladder exercise is one foot on each leg and a struggle to shuffle with the ladder drill two feet on each leg and skiers.